2017
DOI: 10.3171/2017.3.spine161076
|View full text |Cite
|
Sign up to set email alerts
|

Timing and risks of chemoprophylaxis after spinal surgery: a single-center experience with 6869 consecutive patients

Abstract: OBJECTIVEVenous thromboembolism (VTE) after spinal surgery is a major cause of morbidity, but chemoprophylactic anticoagulation can prevent it. However, there is variability in the timing and use of chemoprophylactic anticoagulation after spine surgery, particularly given surgeons’ concerns for spinal epidural hematomas. The goal of this study was to provide insight into the safety, efficacy, and timing of anticoagulation therapy after spinal surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…Sensitivity analysis revealed no significant difference in the results when randomised trials, studies of surgery on trauma patients and anticoagulant regimen other than LMWH exclusively were excluded. Spinal epidural haematoma: There were five studies 19,[26][27][28][29] reporting 49 SEHs in 14,788 patients undergoing spinal surgery for elective indications and trauma. Two studies reported three patients who were discharged with persistent neurological deficits, a C6 quadriplegia, lower extremity weakness and bladder dysfunction 26,28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sensitivity analysis revealed no significant difference in the results when randomised trials, studies of surgery on trauma patients and anticoagulant regimen other than LMWH exclusively were excluded. Spinal epidural haematoma: There were five studies 19,[26][27][28][29] reporting 49 SEHs in 14,788 patients undergoing spinal surgery for elective indications and trauma. Two studies reported three patients who were discharged with persistent neurological deficits, a C6 quadriplegia, lower extremity weakness and bladder dysfunction 26,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported three patients who were discharged with persistent neurological deficits, a C6 quadriplegia, lower extremity weakness and bladder dysfunction 26,28 . Three studies reported that the onset of most SEH events was within a week of surgery, ranging from day 1 to day 56 post operatively 19,27,28 . Pooled analysis of the five studies demonstrated that SEH was found in 0.3% of all patients (49 in 14,788), with 0.2% (32 patients) required surgical evacuation and 0.1% (22 patients) with neurological deficits in both intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current literature on VTE prophylaxis after elective spine surgery is underpowered, 17 heterogeneous, 18 or utilizes nonvalidated surgeon-response metrics. 19 Survey studies by Ploumis et al 20 and Glotzbecker et al 21 criticize the inconsistent application of VTE prophylaxis after high-risk spine procedures, noting that even spinal cord injuries did not clearly delineate common practice.…”
Section: Discussionmentioning
confidence: 99%